Some Aspects of the Modern Understanding of Liberty in Law - Shafalovich, Anna (Teisė, 2019)
In contrast to the philosophical (moral and religious) and psychological side of freedom, the legal side of freedom is poorly studied. This article is intended to fill this gap. As a result of the study, the author reveals the difference between freedom in law and freedom of the individual, reveals their characteristic features, and also substantiates the criterion of differentiation of subjective right and freedom in law.
Keywords: freedom; right; personality; limits of freedom; restriction of freedom